A Fragile Seed of Social and Solidarity Economy in Post-disaster Affected Areas of Tohoku, Japan - Saito, Fumihiko (Calitatea Vieții, 2020)
The world today faces a series of crises, and many observers have started to realize that the root cause of these crises is market capitalism. In such a context, the triple disasters of earthquake, tsunami, and nuclear power plant accident hit the north-eastern part of Japan on 11 March 2011. “3.11” has accelerated the long-term structural changes of rural Japan such as depopulation. Nine years since the disasters, one positive sign is the emergence of networks between producers and consumers who are now reciprocally connected. This article pays particular attention to a new monthly delivery package of magazine and food called, Tohoku Food Communication (TFC), first released in July 2013. The experiences of TFC can be interpreted as a fragile yet significant seed to promote social and solidarity economy (SSE). This paper critically examines both possibilities and limitations of SSE, which may contribute to making our society more sustainable than now.